Sleep and body mass index in infancy and early childhood (6‐36 mo): a longitudinal study. Issue 6 (18th January 2019) - Wang, Lu; Jansen, Wilma; Boere‐Boonekamp, Magda M.; Vlasblom, Eline; L'Hoir, Monique P.; Beltman, Maaike; van Grieken, Amy; Raat, Hein
Summary: Background: Relatively, few longitudinal studies have evaluated the association between sleep and body mass index (BMI) among younger children. In addition, few studies have evaluated the bidirectional longitudinal association between sleep duration and child BMI. Objective: The objective of the study is to determine in children aged 6 to 36 months (1) the cross‐sectional association of sleep duration and sleep problems with child BMI z score, (2) whether sleep duration predicts changes in child BMI z score, and (3) and whether BMI z score can predict changes in child sleep duration. Methods: This study used longitudinal data from the BeeBOFT study (N = 2308). Child sleep duration and sleep problems (indicated by night awakenings and sleep‐onset latency) were parent reported, and child BMI was measured using a standardized protocol by trained healthcare professionals at approximately 6, 14, and 36 months of age. Linear mixed models and linear regression models were applied to assess the cross‐sectional and bidirectional longitudinal associations between sleep and BMI z scores. Results: Cross sectionally, shorter sleep duration was associated with higher BMI z scores at 14 ( β  = −0.034, P  < 0.05) and 36 months ( β  = −0.045, P  < 0.05). Sleep duration at 6 or 14 months did not predict BMI z score at either 14 or 36 months. Higher BMI z scores at 6 months predicted shorter sleep duration (hours) at 14 months ( β  = −0.129, P  < 0.001). No association was found between sleep problems and child BMI z scores. Conclusions: Cross‐sectional associations between shorter sleep duration and higher BMI z score emerged in early childhood (age 14 and 36 mo). Higher BMI z scores may precede shorter sleep duration but not vice versa.